2010
DOI: 10.1007/s10310-009-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomass, and carbon and nitrogen pools in a subtropical evergreen broad-leaved forest in eastern China

Abstract: Subtropical evergreen broad-leaved forest is the most widely distributed land-cover type in eastern China. As the rate of land-use change accelerates worldwide, it is becoming increasingly important to quantify ecosystem biomass and carbon (C) and nitrogen (N) pools. Above and below-ground biomass and ecosystem pools of N and C in a subtropical secondary forest were investigated at Laoshan Mountain Natural Reserve, eastern China. Total biomass was 142.9 Mg ha -1 for a young stand (18 years) and 421.9 Mg ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This link between productivity and climate in subtropical South America implies that with increasing rainfall, the potential for carbon sequestration by native forests increases (Zhang et al. ). While native woodland cover is limited relative to the vast grasslands and agriculture that characterize the Rio de la Plata Basin (Eva et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This link between productivity and climate in subtropical South America implies that with increasing rainfall, the potential for carbon sequestration by native forests increases (Zhang et al. ). While native woodland cover is limited relative to the vast grasslands and agriculture that characterize the Rio de la Plata Basin (Eva et al.…”
Section: Discussionmentioning
confidence: 99%
“…While increasing annual rainfall and declining drought risk in southeastern South America is assumed to provide favourable climate conditions for forest growth, we provide some of the first evidence to show how different native woodland ecosystems in Uruguay respond to climate variability in terms of leaf phenology and productivity. This link between productivity and climate in subtropical South America implies that with increasing rainfall, the potential for carbon sequestration by native forests increases (Zhang et al 2010). While native woodland cover is limited relative to the vast grasslands and agriculture that characterize the Rio de la Plata Basin (Eva et al 2013), forests along riparian corridors are a critical buffer between a terrestrial landscape undergoing rapid agricultural intensification (Achkar et al 2011;Vassallo et al 2013) and a hydrological network that serves as the country's principal source of drinking water and energy (Conde & Sommruga 1999).…”
Section: Discussionmentioning
confidence: 99%
“…C storage in each soil layer was higher than young stands of subtropical, evergreen broadleaved forests in eastern China (12.70, 9.53 and 3.70 Mg C ha -1 in 0-10, 10-30 and 30-50 cm depth respectively) (Zhang et al 2010). Approximately 30% of soil C in the top 100 cm was stored in the 0-20 cm soil layer, which was lower than in a broad-leaved forest (40.9%) (Zhong & Zhao 2001).…”
Section: Soil Carbon Stock Distributionmentioning
confidence: 87%
“…Many ecological studies have reported community structure, composition, biodiversity and C storage assessment of subtropical broadleaved forests (Legendre et al 2009, Zhang et al 2010, Feng et al 2014. There are also studies focused on the relationship between C stocks and biodiversity for temperate (Hatanaka et al 2011) and tropical forests (Williams et al 2008, Cavanaugh et al 2014, Magnago et al 2015.…”
Section: Carbon Distribution and Its Correlation With Floristic Divermentioning
confidence: 99%
“…Permanent plots (30 m × 20 m) were set up in each stands, which were located at the centre to eliminate edge effects. The chronosequence was based on tree-ring counts for at least 15 canopy trees per stand (Zhang et al, 2010a). The general characteristics of the sampling stands are given in Table 1.…”
Section: Study Site Descriptionsmentioning
confidence: 99%